Design, synthesis, structure–activity relationships, and docking studies of pyrazole-containing derivatives as a novel series of potent glucagon receptor antagonists. Issue 12 (15th June 2016) - Shu, Shuangjie; Cai, Xiaoqing; Li, Jia; Feng, Yang; Dai, Antao; Wang, Jiang; Yang, Dehua; Wang, Ming-Wei; Liu, Hong
Graphical abstract: Abstract: Glucagon receptor antagonists possess a great potential for treatment of type 2 diabetes mellitus. A series of pyrazole-containing derivatives were designed, synthesized and evaluated by biological assays as glucagon receptor antagonists. Most of the compounds exhibited good in vitro efficacy. Two of them, compounds17f and17k, displayed relatively potent antagonist effects on glucagon receptors with IC50 values of 3.9 and 3.6 μM, respectively. The possible binding modes of17f and17k with the cognate receptor were explored by molecular docking simulation.